2006
DOI: 10.1007/s00213-006-0570-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower striatal dopamine transporter binding in neuroleptic-naive schizophrenic patients is not related to antipsychotic treatment but it suggests an illness trait

Abstract: Our new series of first-episode naive-schizophrenic patients (1) points out DAT dysfunction as an illness trait due to the significantly lower DAT binding in schizophrenic patients in comparison to healthy subjects; (2) supports the results of other authors who describe PS in never-treated patients; (3) confirms that [(123)I] FP-CIT does not allow us to predict which patients will develop parkinsonism due to the lack of differences between DIP and NoDIP patients; and (4) confirms a null effect of antipsychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 44 publications
7
28
0
Order By: Relevance
“…49 The second study enrolled antipsychotic-naïve first-episode patients and investigated them at baseline and after 4 weeks of risperidone treatment and confirmed a null effect of antipsychotic on striatal DAT density. 42 These results are in line with animal models showing that chronic administration of clozapine, risperidone, or haloperidol did not alter DAT density in rats. 50,51 These consistent results are in interesting contrast to preclinical findings that show that D2 receptors are a critical regulator of synaptic arborization, 52 with pronounced increases in synaptic density seen under chronic D2 blockade 53 and in D2 receptor knockout mice.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…49 The second study enrolled antipsychotic-naïve first-episode patients and investigated them at baseline and after 4 weeks of risperidone treatment and confirmed a null effect of antipsychotic on striatal DAT density. 42 These results are in line with animal models showing that chronic administration of clozapine, risperidone, or haloperidol did not alter DAT density in rats. 50,51 These consistent results are in interesting contrast to preclinical findings that show that D2 receptors are a critical regulator of synaptic arborization, 52 with pronounced increases in synaptic density seen under chronic D2 blockade 53 and in D2 receptor knockout mice.…”
Section: Discussionsupporting
confidence: 79%
“…20,21 Three studies included in the present database uncovered significant striatal DAT decreases in schizophrenic subjects as compared with controls. 34,39,42 The decreased DAT density was attributed to a higher loss of dopamine neuron integrity, in line with the neurotoxic hypothesis of striatal hyperdopaminergia. Conversely, one study found greater DAT density in schizophrenic patients as compared with controls.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…On the other hand, some studies clearly showed a significant decrease of DAT binding in patients with schizophrenia, in young antipsychotic-free patients [41] as well as in chronic medicated patients [42]. Using recent [123I] FP-CIT tracer, in two independent studies, Mateos and co-workers [43,44] reported and confirmed that DAT binding was lower in antipsychotic-naive first episode patients than in healthy subjects, at baseline and after a 4-weektreatment period. Interestingly, in a 4-year follow up study, Mané and co-workers [45] reported a specific relation between striatal DAT number and negative symptoms suggesting that there is a close relationship between DAT number and clinical features of patients.…”
Section: Imaging Striatal Dopamine Transporter (Dat)mentioning
confidence: 76%
“…Laakso et al 51 Mateos et al 59 Schmitt et al 60 Arakawa et al 61 Mateos Figure 3. Studies of dopamine transporter availability.…”
Section: Discussionmentioning
confidence: 99%